2011
DOI: 10.1039/c1jm10492f
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural characterization of cerium doped LYSO sol–gel polycrystal films: potential application as scintillator panel for X-ray imaging

Abstract: The optical and structural properties of sol-gel prepared polycrystalline films of Cerium doped Lutetium and Yttrium oxyorthosilicates (Ce:LYSO) are investigated by means of optical spectroscopy, XRD diffraction and Raman spectroscopy. The sol-gel samples are compared to commercially available Ce-doped LYSO single crystals, and a detailed study of the emission properties from the different cerium sites is performed. The main result is that the polycrystalline films do show very good radioluminescence propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…To date, single crystal or epitaxial thin films with a wide band gap have played an important role in many optoelectronic devices. However, in many cases, bulk or epitaxial layers are replaced by disordered films, especially when cost is one of the most important factors due to their relatively inexpensive fabrication process . Ilmenite‐MgTiO 3 ceramic has a space group R 3true¯ and a rhombohedral crystal system at room temperature, and feature a wide range of applications in microwave integrated circuits and optoelectronic applications .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, single crystal or epitaxial thin films with a wide band gap have played an important role in many optoelectronic devices. However, in many cases, bulk or epitaxial layers are replaced by disordered films, especially when cost is one of the most important factors due to their relatively inexpensive fabrication process . Ilmenite‐MgTiO 3 ceramic has a space group R 3true¯ and a rhombohedral crystal system at room temperature, and feature a wide range of applications in microwave integrated circuits and optoelectronic applications .…”
Section: Introductionmentioning
confidence: 99%
“…However, in many cases, bulk or epitaxial layers are replaced by disordered films, especially when cost is one of the most important factors due to their relatively inexpensive fabrication process. 1,2 Ilmenite-MgTiO 3 ceramic has a space group R 3 and a rhombohedral crystal system at room temperature, 3,4 and feature a wide range of applications in microwave integrated circuits 5,6 and optoelectronic applications. 4,7 However, very few studies have investigated the luminescence properties of undoped MgTiO 3 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, relative fast decay time (ns time range) is preferred. Concerning Ce:YAG, due to the allowed nature of the emission transition in Ce 3+ , the decay constant remains well below 100 ns in YAG [40], and even faster in different matrices [40][41][42][43].…”
Section: Session 2: Properties Of the Phosphormentioning
confidence: 98%
“…Recently great efforts have been dedicated to elucidate the trapping and de‐trapping mechanism of the excited electrical charges in the interaction between high energy radiation and the solid state matrix during the scintillation process . It was suggested that if the trapping effects play a detrimental role in lowering the scintillator efficiency, from a different point of view they can be regarded as potentially useful in storing information via optical writing with X‐ray or deep UV radiation.…”
Section: Introductionmentioning
confidence: 99%